Response to the Variation of Clay Minerals During ASP Flooding in the Saertu Oilfield in the Songliao Basin - Yingjie, Liang; Wenfu, Liang; Wang, He; Zian, Li (Frontiers in Earth Science, 2021)
There are many physical and chemical reactions between pore fluids and rock components in the formation during the alkali-surfactant-polymer (ASP) flooding, especially the strong water-rock reaction of clay minerals. Investigating the variation of clay minerals after ASP flooding is of great significance for the effective development of residual oil in ultra-high water cut stage reservoirs. In this paper, the variation of clay minerals and its influence on reservoir physical properties and residual oil after the ASP flooding are analyzed. The results show that the total amount of clay minerals in reservoirs decrease after ASP flooding in the ultra-high water cut stage reservoirs of the Naner Zone in Saertu oilfield, Songliao Basin. Thereinto, the illite content reduces, while the content of illite smectite mixed -layer and chlorite increase. The content of kaolinite varies greatly. The content of kaolinite decreases in some samples, while the other samples increases. The clay minerals block the pore throat after ASP flooding. As a result, the pore structure coefficient and the seepage tortuosity increase, and the primary intergranular pore throat shrinks and pore-throat coordination number decreases. Nevertheless, the dissolution of clay minerals reduces the pore-throat ratio, and increases the porosity and permeability. The variation of clay minerals after ASP flooding not only intensifies the reservoir heterogeneity, but also affects the formation and distribution of residual oil. The residual oil of oil-clay mixed adsorption state is a newly formed residual oil type related to clay, which accounts for 44.2% of the total residual oil reserves, so it is the main occurrence form of the oil in reservoirs after ASP flooding. Therefore, the exploitation of this type of residual oil has great significance to enhance the oil recovery in ultra-high water cut stage reservoirs.